Strength and conditioning for competitive rowers - Nugent, F. J.; Flanagan, E. P.; Wilson, F.; Warrington, G. D. (Strength and Conditioning Journal, 2020)
Strength and conditioning (S&C) is an essential component of performance enhancement and injury reduction for competitive rowers. However, information regarding the practical application of appropriate S&C programming for competitive rowers is limited. The aim of this article is to provide an evidence-based needs analysis based on a review of the literature in the area of biomechanics, physiology, and injury epidemiology in the sport of rowing. Practical considerations and guidelines for the implementation of S&C programs for competitive rowers will be provided